2022
DOI: 10.3389/fmed.2022.1019434
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID-19 pandemic and wearing face masks on ophthalmology practice: What is known so far? A narrative review

Abstract: Face masks, along with other preventive measures, can help slow the spread of COVID-19. Despite the positive effect of the mask in combating the virus, it has some negative effects on the human body that must be followed up on and reduced. In this study, we discuss the impact of wearing face masks on the eye and the common issues associated with using them. The literature search was conducted using electronic databases such as PubMed and Google Scholar. Only articles published in English were included. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The widespread use of face masks as a method of preventing coronavirus transmission has been a change in ophthalmic clinical practice since the onset of the SARS-CoV-2 pandemic. 2 It is of great importance to determine whether its use can increase the risk of postintravitreal injection endophthalmitis (PIE) because of the devastating prognosis of this disease.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…The widespread use of face masks as a method of preventing coronavirus transmission has been a change in ophthalmic clinical practice since the onset of the SARS-CoV-2 pandemic. 2 It is of great importance to determine whether its use can increase the risk of postintravitreal injection endophthalmitis (PIE) because of the devastating prognosis of this disease.…”
Section: To the Editormentioning
confidence: 99%
“…In practice, we observed retrograde airflow from the top of patient masks and subsequent studies found a higher burden of oral flora exposure to the ocular surface as a result. 2,3 It was, however, unclear whether such exposure did in fact increase infection risk. Contrarily, pandemic guidelines also increased rates of provider and ancillary staff mask use, which in turn could decrease oral flora exposure.…”
Section: Replymentioning
confidence: 99%